PENGARUH SIMPANAN ANGGOTA DAN PINJAMAN ANGGOTA TERHADAP SISA HASIL USAHA PADA KOPERASI SIMPAN PINJAM AGUNG KENCANA KOTA SUKABUMI - Levina, Levina (Universitas Muhammadiyah Tangerang, 2023)
This study aims to determine the effect of member savings and member loans on the remaining operating results. The variables used in this study are member savings, member loans and the remaining operating results. This research was conducted at the Agung Kencana Savings and Loan Cooperative, Sukabumi City for the 2015-2020 period. The research method used is a quantitative method with an associative approach. The population and sample collection technique in this study used the saturated sampling method. The data analysis used is non-parametric with multiple linear analysis. With the results of the research, Member Deposits have a positive and significant effect on the Remaining Operating Income with a significance of 0.000 <0.05 and tcount > ttable (5,820 > 1,668), Member Loans have a positive and significant effect on the Remaining Operating Results with a significance of 0.000 > 0.05 and tcount > ttable (4,430 >1,668), and Member Savings, Member Loans have a simultaneous effect on Remaining Operating Results with a significance of 0.000 > 0.05 and Fcount > Ftable (64.956 > 3.138). The contribution of member savings and member loans to the remaining operating results is 66.7%.